Influence of steel fiber types on residual mechanical properties and explosive spalling of hybrid fiber reinforced ultra-high performance concrete: Optimization and evaluations - Rui-Yu Ma; Juan Yang; Gai-Fei Peng (Case Studies in Construction Materials, 2023)
To investigate the influence of steel fiber on improving the high-temperature resistance of hybrid fiber-reinforced ultra-high performance concrete (UHPC), four types of UHPC specimens were prepared. The residual strength and fracture energy of all UHPCs were determined after exposure to varying high temperatures, and internal temperature in the specimens were also measured. Additionally, explosive spalling tests were performed on specimens with different moisture contents. The results indicate that the residual mechanical properties of UHPC initially increase and subsequently decrease as the target temperature increases. Notable differences in thermal conductivity were observed among the tested UHPC specimens. As the moisture content of the specimens increased, the likelihood and severity of explosive spalling in the specimens increased. Corrugated high-strength steel fibers, measuring 35 mm in length and 1 mm in diameter, are highly effective at preventing explosive spalling of UHPC, and high-temperature treated recycled steel fiber from tires also exhibits better performance than other two types of steel fiber. High tensile strength of steel fiber and its distinctive corrugated appearance can be the primary contributing factors. Furthermore, two established computational models which demonstrated a significant level of congruence were employed for evaluating explosive spalling and anti-spalling properties of UHPC specimens. This suggests that cracking resistance provided by steel fiber plays an important role in preventing the explosive spalling of UHPC, emphasizing the importance of exploring specific steel fiber based on its appearance and tensile strength.